Intertwined burdens: exploring the relationship between menstruation, social status, and hysterectomy among agrarian women in India - Manjari Sinha; Manesh Muraleedharan (Discover Social Science and Health)
Abstract In Indian rural areas, particularly among rural agrarian women, the challenges of managing menstruation extend beyond physical discomfort. The discourse surrounding menstruation has sparked significant attention, with terms like “period poverty,” “menstrual equity,” and “period stigma” gaining prominence. Hysterectomy, a surgical option, is increasingly prescribed by doctors, even for conditions like heavy menstrual bleeding that could potentially be addressed with oral medication or injections. This study examines the relationship between rural Indian women’s living and working conditions and their experiences with gynecological issues, with a particular focus on those that may lead to hysterectomy. Employing a qualitative paradigm with a phenomenological approach, the research explores the narratives of 38 women who have undergone hysterectomies. Findings underscore the significant impact of menstrual discomfort on women’s daily activities, leading to delayed health acknowledgment and treatment-seeking. The study advocates for policies promoting informed consent, shared decision-making, and stricter regulations on hysterectomy procedures.